An Overview of the Evolution of the Porous Silicon material: A review - Ghazwan Ali; Marwan Hafeedh Younus; Ivan Karomi (College of Education for Pure Sciences, 2021)
Recently, the properties and applications of the porous became the main subject of several books and the vast numbers of review articles. Porous silicon has demonstrated significant versatility and promise for a wide range of optoelectronic applications thanks to its large surface area and intense photoluminescence at room temperature. In this review, we describe the fabrication techniques and experimental improvements made towards porous silicon (PSi) and we provide a full picture of realization and characterization of this material. We also highlight its important properties, such as chemical, structure and surface properties. We summarize the techniques that have been used, including Fourier transform infrared spectroscopy, X-ray diffraction measurements, atomic force microscope images (AFM) and a scanning probe microscope (SEM). Additionally, the effect of the current density and etching time are also documented in this review. In summary, porous silicon has undergone vast improvement in both fabrication and characterization methods, which makes it an attractive modern material.